American pistol shooting - Frazer, William David 1884- (Skyhouse Publishing, 2015)
Skyhorse Publishing is proud to publish a broad range of books for hunters and firearms enthusiasts. We publish books about shotguns, rifles, handguns, target shooting, gun collecting, self-defense, archery, ammunition, knives, gunsmithing, gun repair, and wilderness survival. We publish books on deer hunting, big game hunting, small game hunting, wing shooting, turkey hunting, deer stands, duck blinds, bowhunting, wing shooting, hunting dogs, and more. While not every title we publish becomes a New York Times bestseller or a national bestseller, we are committed to publishing books on subjects that are sometimes overlooked by other publishers and to authors whose work might not otherwise find a home.